Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 652 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Marsilea strigosa Willd." ] } The dataset includes 652 records from 48 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002635-150221044754056/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences